2019
DOI: 10.1098/rsos.191077
|View full text |Cite
|
Sign up to set email alerts
|

Rapid preparation of terbium-doped titanium dioxide nanoparticles and their enhanced photocatalytic performance

Abstract: Further applications of photocatalysis were limited by the high recombination probability of photo-induced electron–hole pairs in traditional titanium dioxide nanoparticles (TiO2 NPs). Herein, we modified them with rare earth metal via a facile sol–gel method, using tetrabutyl titanate as a precursor and terbium (III) nitrate hexahydrate as terbium (Tb) source. The resulting samples with different Tb doping amounts (from 0 to 2%) have been characterized by X-ray diffraction, UV–visible diffuse reflectance spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…In the case of the bixbyte structure, Tb 3+ oxidizes easily due to the presence of oxygen vacancies in the crystal lattice [26]. In Tbdoped anatase photocatalysts prepared by sol-gel from terbium (III) nitrate hexahydrate and tetrabutyl titanate and calcined at 500ºC for 4 h Tb 4+ and Tb 3+ were also detected by XPS [13]. Those catalysts are similar materials than those studied in this work and also prepared by sol-gel.…”
Section: Morphology and Structure Of 550 ºC Calcined Samplessupporting
confidence: 55%
See 1 more Smart Citation
“…In the case of the bixbyte structure, Tb 3+ oxidizes easily due to the presence of oxygen vacancies in the crystal lattice [26]. In Tbdoped anatase photocatalysts prepared by sol-gel from terbium (III) nitrate hexahydrate and tetrabutyl titanate and calcined at 500ºC for 4 h Tb 4+ and Tb 3+ were also detected by XPS [13]. Those catalysts are similar materials than those studied in this work and also prepared by sol-gel.…”
Section: Morphology and Structure Of 550 ºC Calcined Samplessupporting
confidence: 55%
“…Furthermore, terbium is adequate for the fabrication of visible light emitting devices, because of its usually intense intra-4f transitions at wavelengths in the visible range 400-600 nm [10]. In previous studies, Tb-doped TiO2 thin films and bulk materials have been prepared but not hollow spheres [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…It is clearly observed that while N doping effectively narrowed the band gap of the undoped TiO 2 nanocrystals by 0.32 eV, further doping of the N-TiO 2 nanocrystals with Tb only slightly widened the band gap of the N-TiO 2 nanocrystals by 0.1 eV, which can be attributed to their smaller sizes compared with the N-TiO 2 nanocrystals. 30,31 This also implies that Tb resided mostly at the crystal boundary of TiO 2 nanocrystals, and did not have a significant impact on the band structure of the TiO 2 nanocrystals.…”
Section: Resultsmentioning
confidence: 93%
“…This approach was used in [38], where the titanium (IV) oxide modification by europium resulted in a significant improvement in photoactivity (degradation occurs under sunlight in natural conditions). Other researchers [39] found an increase in the dye degradation rate (at least 3 times) during the photocatalytic process of erbium-modified titanium (IV) oxide.…”
Section: Literature Review and Problem Statementmentioning
confidence: 89%